A BRIEF NOTE ON PALLEY’S CRITICISM OF NEW DEVELOPMENTALISM - Oreiro, José Luis; de Paula, Luiz Fernando (Investigación Económica, 2022)
This short paper offers some critical remarks on Palley’s critical assessment of New Developmentalism. It argues that Palley’s criticism is based on a narrow view of the Brazilian New Developmentalist school and largely ignores the work of other members of this school and even other writings by Bresser-Pereira. This “original sin” in Palley’s assessment leads him to associate New-Developmentalism unfairly with Neo-Liberalism, as well as setting up a false opposition between Classical Developmentalism and New Developmentalism, rather than seeing both as strands of developmental theory designed for different historical phases of Latin American development. UNA BREVE NOTA SOBRE LA CRÍTICA DE PALLEY AL NUEVO DESARROLLO RESUMEN Este breve artículo ofrece algunas observaciones críticas sobre la valoración que hace Palley del nuevo desarrollismo. Sostiene que la crítica de Palley se basa en una visión estrecha de la escuela brasileña del nuevo desarrollismo e ignora en gran medida el trabajo de otros miembros de esta escuela e incluso otros escritos de Bresser-Pereira. Este “pecado original” en la evaluación de Palley le lleva a asociar injustamente el nuevo desarrollismo con el neoliberalismo, así como a establecer una falsa oposición entre el desarrollismo clásico y el nuevo desarrollismo, en lugar de ver ambos como vertientes de la teoría del desarrollo diseñadas para diferentes fases históricas del desarrollo latinoamericano.